Ti-mn alloy catalyzed mgh2 composite hydrogen storage material and preparation method thereof

CN122916045APending Publication Date: 2026-10-16CHONGQING INST OF NEW ENE STOR MATER & EQUIP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611267558.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

(1)现有技术多采用三元或多元合金体系,合金制备工艺复杂、成本较高;

Benefits of technology

(1)显著降低放氢温度:本发明采用C14型Laves相结构的Ti1+xMn2-x(0.15≤x≤0.25),Ti-Mn合金本身属于AB2型室温可逆储氢合金,依靠自身储氢本征特性从多维度催化MgH2低温放氢:第一,钛锰氢化物作为氢中间载体拆分脱氢反应路径,降低单步反应活化能;第二,循环储氢带来氢致体积形变,动态构建氢扩散缺陷通道;第三,合金表层固有的氢结合特性加速氢气析出。二元合金与MgH2粉末通过球磨复合,依托储氢属性带来的协同效果,可显著降低MgH2的初始放氢温度至175℃,大幅拓展了MgH2在中低温条件下的实际应用可能性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916045A_ABST
    Figure CN122916045A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of solid-state hydrogen storage materials, and discloses a Ti-Mn alloy catalyzed MgH2 composite hydrogen storage material and a preparation method thereof. 1+x Mn 2‑x , 0.15≤x≤0.25, the Ti-Mn alloy accounts for 10wt% of the mass of MgH2. The preparation method comprises the following steps: preparing a Ti-Mn alloy ingot by arc melting; mechanically crushing and hydrogen absorption and release pulverization to obtain alloy powder; and ball milling the Ti-Mn alloy and MgH2 powder to be compounded. The application significantly reduces the hydrogen release temperature of MgH2 by optimizing the Ti / Mn ratio, and the effect is optimal when x=0.20, the hydrogen release temperature is reduced to 175 DEG C, and 98% of the capacity is released at 250 DEG C in only 13.5 minutes. The application has the advantages of simple alloy composition, low cost, excellent catalytic effect, good controllability of the preparation process and the like, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid-state hydrogen storage materials technology, specifically relating to a Ti-Mn alloy-catalyzed MgH2 composite hydrogen storage material and its preparation method. Background Technology

[0002] Among many solid hydrogen storage materials, magnesium hydride (MgH2) is considered one of the most promising solid hydrogen storage materials due to its outstanding advantages such as a theoretical hydrogen storage density of up to 7.6 wt%, good reversibility of hydrogen absorption and desorption processes, abundant magnesium reserves in the Earth's crust, and low cost. It has broad potential application value in fields such as hydrogen sources for vehicle fuel cells, distributed energy storage, and portable hydrogen supply.

[0003] However, pure MgH2 faces two major challenges in practical applications: First, its thermodynamic stability is too high, and the bond energy of the Mg-H bond is strong, requiring the hydrogen desorption reaction to proceed at high temperatures. The initial hydrogen desorption temperature of pure MgH2 is typically above 300℃, far exceeding the conventional operating temperature range of downstream applications such as proton exchange membrane fuel cells, resulting in low system energy utilization efficiency. Second, pure MgH2 exhibits poor hydrogen absorption and desorption kinetics, with a slow reaction rate, making it difficult to meet the practical application requirements for rapid hydrogen charging and desorption. These two major problems severely restrict the large-scale commercial application of MgH2.

[0004] To improve the hydrogen storage performance of MgH2, researchers have explored various modification strategies, among which the addition of catalysts is one of the more effective methods. Ti-based catalysts can effectively lower the kinetic energy barrier of MgH2 and improve its hydrogen absorption / desorption kinetics. Currently, there are reports on the composite of Ti-Mn alloys with MgH2, but these techniques still have the following limitations: (1) Existing technologies mostly use ternary or multi-element alloy systems, and the alloy preparation process is complex and costly; (2) The hydrogen desorption temperature of existing Ti-Mn alloy / MgH2 composite materials is still relatively high (usually ≥190℃), and the catalytic efficiency needs to be further improved; (3) The regulation of the catalytic effect by the alloy composition ratio was not considered. Summary of the Invention

[0005] In view of this, the purpose of this invention is to solve the above problems and provide a Ti-Mn alloy-catalyzed MgH2 composite hydrogen storage material and its preparation method.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A Ti-Mn alloy-catalyzed MgH2 composite hydrogen storage material is disclosed. The composite hydrogen storage material is prepared by ball milling MgH2 powder and Ti-Mn alloy powder. The Ti-Mn alloy has a C14 type Laves phase structure and its general chemical formula is Ti. 1+ x Mn 2-x , where 0.15≤x≤0.25.

[0007] Furthermore, the mass of the Ti-Mn alloy powder in the composite hydrogen storage material is 10 wt% of the mass of the MgH2 powder.

[0008] Furthermore, in the general chemical formula of the Ti-Mn alloy, x = 0.2.

[0009] A method for preparing the Ti-Mn alloy-catalyzed MgH2 composite hydrogen storage material as described above includes the following steps: (1) Preparation of Ti-Mn alloy ingots: according to the chemical formula Ti 1+x Mn 2-x Titanium and manganese raw materials were weighed according to the stoichiometric ratio, with an additional 5 wt% of Mn added. They were placed in an electric arc melting furnace and electric arc melting was carried out under an argon protective atmosphere. The melting was carried out 4 times. Then, the materials were vacuum heat-treated at 1100℃ for 3 hours to obtain Ti-Mn alloy ingots with C14 type Laves phase structure. (2) Preparation of Ti-Mn alloy powder: The Ti-Mn alloy ingot obtained in step (1) is mechanically crushed and pulverized three times under a hydrogen pressure of 4MPa to obtain Ti-Mn alloy powder. (3) Ball milling composite: The Ti-Mn alloy powder obtained in step (2) is mixed with MgH2 powder in proportion, placed in a planetary ball mill, and ball milled at a speed of 400 rpm for 5 hours under a protective atmosphere to obtain the Ti-Mn alloy catalyzed MgH2 composite hydrogen storage material.

[0010] Furthermore, the purity of the argon gas mentioned in step (1) is ≥99.99%.

[0011] Furthermore, the current for arc melting in step (1) is 100~150A.

[0012] Further, in step (3), the Ti-Mn alloy powder and MgH2 powder are mixed at a ratio where the mass of Ti-Mn alloy powder is 10 wt% of the mass of MgH2 powder.

[0013] Furthermore, the protective atmosphere described in step (3) is an argon atmosphere.

[0014] Furthermore, the ball-to-material ratio in the ball milling process described in step (3) is 30:1.

[0015] The beneficial effects of this invention are as follows: (1) Significantly reduced hydrogen desorption temperature: This invention uses Ti with a C14 type Laves phase structure 1+x Mn 2-x (0.15≤x≤0.25), the Ti-Mn alloy itself belongs to the AB2 type room temperature reversible hydrogen storage alloy. Relying on its intrinsic hydrogen storage properties, it catalyzes the low-temperature hydrogen release of MgH2 from multiple dimensions: First, the titanium manganese hydride acts as an intermediate hydrogen carrier, splitting the dehydrogenation reaction pathway and reducing the activation energy of the single-step reaction; second, the cyclic hydrogen storage brings about hydrogen-induced volume deformation, dynamically constructing hydrogen diffusion defect channels; third, the inherent hydrogen binding properties of the alloy surface accelerate hydrogen evolution. The binary alloy and MgH2 powder are ball-milled and combined, relying on the synergistic effect brought by the hydrogen storage properties, which can significantly reduce the initial hydrogen release temperature of MgH2 to 175℃, greatly expanding the practical application possibilities of MgH2 under medium and low temperature conditions.

[0016] (2) Excellent hydrogen desorption kinetics: By optimizing the Ti / Mn ratio, the composite hydrogen storage material of this invention exhibits rapid hydrogen desorption kinetics at moderate temperatures. The catalytic effect is optimal when x=0.20. This composite hydrogen storage material releases 98% of its capacity in only 13.5 minutes at 250℃ and 98% of its capacity in only 2.9 minutes at 300℃, which is significantly better than the kinetic performance of pure MgH2 at the same temperature.

[0017] (3) The alloy composition is simple and the cost is low: The present invention uses a binary Ti-Mn alloy as a catalyst. Compared with the ternary or multi-element alloy system widely used in the prior art, there are fewer types of raw materials, the supply chain is simple, and the raw material cost is low. At the same time, the smelting process of binary alloy is easier to control, the composition uniformity is better guaranteed, the preparation difficulty is reduced, and it is conducive to large-scale production.

[0018] (4) The catalytic effect can be precisely controlled by the components: This invention systematically reveals that Ti 1+x Mn 2-x The effect of the Ti / Mn ratio in the alloy on the catalytic performance of MgH2 shows a trend of first increasing and then decreasing within the range of x = 0.15 to 0.25, with the optimal catalytic effect observed at x = 0.20. This pattern provides a clear direction for catalyst composition design, allowing performance to be predicted and controlled by precisely adjusting the stoichiometric ratio.

[0019] Other advantages, objectives, and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination, or may be learned from practice of the invention. The objectives and other advantages of the invention can be realized and obtained through the following description. Attached Figure Description

[0020] To make the objectives, technical solutions, and advantages of the present invention clearer, the preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings, wherein: Figure 1 The temperature-dependent hydrogen release curves for different hydrogen storage materials in each embodiment are shown.

[0021] Figure 2 For Ti 1.15 Mn 1.85 Hydrogen desorption kinetics curves of MgH2 composite hydrogen storage material catalyzed by alloy at different temperatures.

[0022] Figure 3 For Ti 1.20 Mn 1.80 Hydrogen desorption kinetics curves of MgH2 composite hydrogen storage material catalyzed by alloy at different temperatures.

[0023] Figure 4 For Ti 1.25 Mn 1.75 Hydrogen desorption kinetics curves of MgH2 composite hydrogen storage material catalyzed by alloy at different temperatures.

[0024] Figure 5 The figures show the hydrogen desorption kinetics of MgH2 at different temperatures.

[0025] Figure 6 The hydrogen desorption kinetics curves of different hydrogen storage materials at 250 °C are shown.

[0026] Figure 7 The hydrogen desorption kinetics curves of different hydrogen storage materials at 300 °C are shown. Detailed Implementation

[0027] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments are only schematic representations of the basic concept of the present invention. Unless otherwise specified, the following embodiments and features can be combined with each other.

[0028] The accompanying drawings are for illustrative purposes only and are schematic diagrams, not actual pictures. They should not be construed as limiting the invention. To better illustrate the embodiments of the invention, some parts in the drawings may be omitted, enlarged, or reduced, and do not represent the actual product dimensions. It is understandable to those skilled in the art that some well-known structures and their descriptions may be omitted in the drawings.

[0029] In the accompanying drawings of the embodiments of the present invention, the same or similar reference numerals correspond to the same or similar components. In the description of the present invention, it should be understood that if terms such as "upper," "lower," "left," "right," "front," and "rear" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings, they are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, the terms used to describe positional relationships in the drawings are only for illustrative purposes and should not be construed as limiting the present invention. For those skilled in the art, the specific meaning of the above terms can be understood according to the specific circumstances.

[0030] Example 1: Ti 1.15 Mn 1.85 Alloy-catalyzed MgH2 composite hydrogen storage materials This embodiment provides a Ti 1.15 Mn 1.85 Alloy-catalyzed MgH2 composite hydrogen storage materials and their preparation methods, wherein the Ti-Mn alloy has a C14 type Laves phase structure and the chemical formula is Ti. 1.15 Mn 1.85 The mass of Ti-Mn alloy powder is 10 wt% of the mass of MgH2 powder.

[0031] The specific preparation method includes the following steps: (1) Preparation of Ti 1.15 Mn 1.85 Alloy ingots: according to the chemical formula Ti 1.15 Mn 1.85 Pure titanium and pure manganese raw materials were weighed according to stoichiometric ratios, with an additional 5 wt% of manganese added to compensate for volatilization losses during the smelting process. The raw materials were placed in a copper crucible in a non-consumable vacuum arc melting furnace. After evacuation, high-purity argon gas (purity ≥99.99%) was introduced to a negative pressure state, and arc melting was carried out under argon protection at a melting current of 150A. After each melting, the ingot was turned over to ensure uniform composition. A total of 4 meltings were performed, followed by vacuum heat treatment at 1100℃ for 3 hours to obtain Ti with a C14 type Laves phase structure and uniform composition. 1.15 Mn 1.85 Alloy ingots.

[0032] (2) Preparation of Ti 1.15 Mn 1.85 Alloy powder: The Ti obtained in step (1) 1.15 Mn 1.85 The alloy ingot was mechanically crushed and pulverized three times under a hydrogen pressure of 4 MPa, followed by hydrogen absorption and desorption. The pulverized powder was then passed through a 200-mesh sieve to obtain Ti. 1.15 Mn 1.85 alloy powder.

[0033] (3) Ball milling composite: The Ti obtained in step (2) 1.15 Mn 1.85 Alloy powder and MgH2 powder were mixed at a ratio of Ti-Mn alloy powder to 10 wt% of MgH2 powder. The mixture was placed in the grinding jar of a planetary ball mill under an argon protective atmosphere. Stainless steel grinding balls were added at a ball-to-powder ratio of 30:1, and the mixture was ball-milled at 400 rpm for 5 hours to obtain Ti. 1.15 Mn 1.85 Alloy-catalyzed MgH2 composite hydrogen storage material.

[0034] The hydrogen storage performance of the above-mentioned composite hydrogen storage material was tested using a Sieverts-type PCT testing device. The test results showed that the initial hydrogen release temperature of the material was 175 °C; it took 4.4 minutes to release 98% of its capacity at 300 °C; 7.8 minutes to release 98% of its capacity at 275 °C; and 22.0 minutes to release 98% of its capacity at 250 °C. Its temperature-dependent hydrogen release curve is shown below. Figure 1 As shown, the hydrogen desorption kinetic curves at different temperatures are as follows: Figure 2 As shown.

[0035] Example 2: Ti 1.20 Mn 1.80 Alloy-catalyzed MgH2 composite hydrogen storage materials This embodiment provides a Ti 1.20 Mn 1.80 Alloy-catalyzed MgH2 composite hydrogen storage materials and their preparation methods, wherein the Ti-Mn alloy has a C14 type Laves phase structure and the chemical formula is Ti. 1.20 Mn 1.80 The mass of Ti-Mn alloy powder is 10 wt% of the mass of MgH2 powder.

[0036] The specific preparation method includes the following steps: (1) Preparation of Ti 1.20 Mn 1.80 Alloy ingots: according to the chemical formula Ti 1.20 Mn 1.80 Pure titanium and pure manganese raw materials were weighed according to stoichiometric ratios, with an additional 5 wt% of manganese added to compensate for volatilization losses during the smelting process. The raw materials were placed in a copper crucible in a non-consumable vacuum arc melting furnace. After evacuation, high-purity argon gas (purity ≥99.99%) was introduced to a negative pressure state, and arc melting was carried out under argon protection at a melting current of 150A. After each melting, the ingot was turned over to ensure uniform composition. A total of 4 meltings were performed, followed by vacuum heat treatment at 1100℃ for 3 hours to obtain Ti with a C14 type Laves phase structure and uniform composition. 1.20 Mn 1.80 Alloy ingots.

[0037] (2) Preparation of Ti 1.20 Mn 1.80 Alloy powder: The Ti obtained in step (1) 1.20 Mn 1.80 The alloy ingot was mechanically crushed and pulverized three times under a hydrogen pressure of 4 MPa, followed by hydrogen absorption and desorption. The pulverized powder was then passed through a 200-mesh sieve to obtain Ti. 1.20 Mn 1.80 alloy powder.

[0038] (3) Ball milling composite: The Ti obtained in step (2) 1.20 Mn 1.80 Alloy powder and MgH2 powder were mixed at a ratio of Ti-Mn alloy powder to 10 wt% of MgH2 powder. The mixture was placed in the grinding jar of a planetary ball mill under an argon protective atmosphere. Stainless steel grinding balls were added at a ball-to-powder ratio of 30:1, and the mixture was ball-milled at 400 rpm for 5 hours to obtain Ti. 1.20 Mn 1.80 Alloy-catalyzed MgH2 composite hydrogen storage material.

[0039] The hydrogen storage performance of the above-mentioned composite hydrogen storage material was tested using a Sieverts-type PCT testing device. The test results showed that the initial hydrogen release temperature of the material was 175℃; it took 2.9 minutes to release 98% of its capacity at 300℃; 5.3 minutes to release 98% of its capacity at 275℃; and 13.5 minutes to release 98% of its capacity at 250℃. Its temperature-dependent hydrogen release curve is shown below. Figure 1 As shown, the hydrogen desorption kinetic curves at different temperatures are as follows: Figure 3 As shown.

[0040] Example 3: Ti 1.25 Mn 1.75 Alloy-catalyzed MgH2 composite hydrogen storage materials This embodiment provides a Ti 1.25 Mn 1.75 Alloy-catalyzed MgH2 composite hydrogen storage materials and their preparation methods, wherein the Ti-Mn alloy has a C14 type Laves phase structure and the chemical formula is Ti. 1.25 Mn 1.75 The mass of Ti-Mn alloy powder is 10 wt% of the mass of MgH2 powder.

[0041] The specific preparation method includes the following steps: (1) Preparation of Ti 1.25 Mn 1.75 Alloy ingots: according to the chemical formula Ti 1.25 Mn 1.75Pure titanium and pure manganese raw materials were weighed according to stoichiometric ratios, with an additional 5 wt% of manganese added to compensate for volatilization losses during the smelting process. The raw materials were placed in a copper crucible in a non-consumable vacuum arc melting furnace. After evacuation, high-purity argon gas (purity ≥99.99%) was introduced to a negative pressure state, and arc melting was carried out under argon protection at a melting current of 150A. After each melting, the ingot was turned over to ensure uniform composition. A total of 4 meltings were performed, followed by vacuum heat treatment at 1100℃ for 3 hours to obtain Ti with a uniform composition and C14 type Laves phase structure. 1.25 Mn 1.75 Alloy ingots.

[0042] (2) Preparation of Ti 1.25 Mn 1.75 Alloy powder: The Ti obtained in step (1) 1.25 Mn 1.75 The alloy ingot was mechanically crushed and pulverized three times under a hydrogen pressure of 4 MPa, followed by hydrogen absorption and desorption. The pulverized powder was then passed through a 200-mesh sieve to obtain Ti. 1.25 Mn 1.75 alloy powder.

[0043] (3) Ball milling composite: The Ti obtained in step (2) 1.25 Mn 1.75 Alloy powder and MgH2 powder were mixed at a ratio of Ti-Mn alloy powder to 10 wt% of MgH2 powder. The mixture was placed in the grinding jar of a planetary ball mill under an argon protective atmosphere. Stainless steel grinding balls were added at a ball-to-powder ratio of 30:1, and the mixture was ball-milled at 400 rpm for 5 hours to obtain Ti. 1.25 Mn 1.75 Alloy-catalyzed MgH2 composite hydrogen storage material.

[0044] The hydrogen storage performance of the above-mentioned composite hydrogen storage material was tested using a Sieverts-type PCT testing device. The test results showed that the initial hydrogen release temperature of the material was 175℃; it took 4.1 minutes to release 98% of its capacity at 300℃; 7.1 minutes at 275℃; and 17.6 minutes at 250℃. Its temperature-dependent hydrogen release curve is shown below. Figure 1 As shown, the hydrogen desorption kinetic curves at different temperatures are as follows: Figure 4 As shown.

[0045] Comparative Example 1: Pure MgH2 (without catalyst) Using MgH2 milled under the same conditions as a control, no Ti-Mn alloy catalyst was added. The specific method was as follows: MgH2 powder was placed in the grinding jar of a planetary ball mill under an argon protective atmosphere, and stainless steel grinding balls were added at a ball-to-powder ratio of 30:1. The mixture was ball-milled at 400 rpm for 5 hours to obtain ball-milled MgH2.

[0046] The hydrogen storage performance of the ball-milled MgH2 was tested using a Sieverts-type PCT testing apparatus. The results showed that its initial hydrogen release temperature was 275℃, 100℃ higher than that of the Ti-Mn alloy-catalyzed MgH2 in Examples 1-3; it could not completely release hydrogen within 30 minutes at both 280℃ and 300℃; even at 325℃, it still took 17.3 minutes to release 98% of its capacity. Its temperature-dependent hydrogen release curve is shown below. Figure 1 As shown, the hydrogen desorption kinetic curves at different temperatures are as follows: Figure 5 As shown.

[0047] like Figure 6 and Figure 7 As shown, by comparing the hydrogen desorption kinetics curves of MgH2 composite hydrogen storage materials catalyzed by Ti-Mn alloys with different Ti / Mn ratios in Examples 1-3 at 250℃ and 300℃, it can be seen that: At 250°C, Example 2 (x=0.20, Ti) 1.20 Mn 1.80 The time taken to release 98% of the capacity was 13.5 minutes, significantly shorter than that of Example 1 (x=0.15, Ti). 1.15 Mn 1.85 ) for 22.0 minutes and Example 3 (x=0.25, Ti 1.25 Mn 1.75 17.6 minutes.

[0048] At 300°C, Example 2 took 2.9 minutes to release 98% of its capacity, which was significantly shorter than 4.4 minutes in Example 1 and 4.1 minutes in Example 3.

[0049] The above results indicate that in Ti 1+x Mn 2-x In the alloy, the catalytic effect on the hydrogen desorption kinetics of MgH2 is optimal when x=0.20, and the hydrogen desorption rate is the fastest, which is the best embodiment of the present invention.

[0050] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A Ti-Mn alloy-catalyzed MgH2 composite hydrogen storage material, characterized in that: The composite hydrogen storage material is prepared by ball milling MgH2 powder and Ti-Mn alloy powder. The Ti-Mn alloy has a C14 type Laves phase structure and its general chemical formula is Ti. 1+x Mn 2-x , where 0.15≤x≤0.

25.

2. The Ti-Mn alloy-catalyzed MgH2 composite hydrogen storage material according to claim 1, characterized in that: The mass of the Ti-Mn alloy powder in the composite hydrogen storage material is 10 wt% of the mass of the MgH2 powder.

3. The Ti-Mn alloy-catalyzed MgH2 composite hydrogen storage material according to claim 1, characterized in that: In the general chemical formula of the Ti-Mn alloy, x = 0.

2.

4. A method for preparing the Ti-Mn alloy-catalyzed MgH2 composite hydrogen storage material according to any one of claims 1-3, characterized in that, Includes the following steps: (1) Preparation of Ti-Mn alloy ingots: according to the chemical formula Ti 1+x Mn 2-x Titanium and manganese raw materials were weighed according to the stoichiometric ratio, with an additional 5 wt% of Mn added. They were placed in an electric arc melting furnace and electric arc melting was carried out under an argon protective atmosphere. The melting was carried out 4 times. Then, the materials were vacuum heat-treated at 1100℃ for 3 hours to obtain Ti-Mn alloy ingots with C14 type Laves phase structure. (2) Preparation of Ti-Mn alloy powder: The Ti-Mn alloy ingot obtained in step (1) is mechanically crushed and pulverized three times under a hydrogen pressure of 4MPa to obtain Ti-Mn alloy powder. (3) Ball milling composite: The Ti-Mn alloy powder obtained in step (2) is mixed with MgH2 powder in proportion, placed in a planetary ball mill, and ball milled for 5 hours at a speed of 400 rpm under a protective atmosphere to obtain the Ti-Mn alloy catalyzed MgH2 composite hydrogen storage material.

5. The method according to claim 4, characterized in that: The purity of the argon gas mentioned in step (1) is ≥99.99%.

6. The method according to claim 4, characterized in that: The current for arc melting in step (1) is 100~150A.

7. The method according to claim 4, characterized in that: In step (3), the Ti-Mn alloy powder and MgH2 powder are mixed at a ratio of 10 wt% of the mass of Ti-Mn alloy powder to the mass of MgH2 powder.

8. The method according to claim 4, characterized in that: The protective atmosphere mentioned in step (3) is an argon atmosphere.

9. The method according to claim 4, characterized in that: The ball-to-material ratio in step (3) is 30:1.